2015
DOI: 10.1242/bio.201410249
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of detergent-insoluble membranes in pollen tubes of Nicotiana tabacum (L.)

Abstract: Pollen tubes are the vehicle for sperm cell delivery to the embryo sac during fertilisation of Angiosperms. They provide an intriguing model for unravelling mechanisms of growing to extremes. The asymmetric distribution of lipids and proteins in the pollen tube plasma membrane modulates ion fluxes and actin dynamics and is maintained by a delicate equilibrium between exocytosis and endocytosis. The structural constraints regulating polarised secretion and asymmetric protein distribution on the plasma membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 181 publications
0
22
0
Order By: Relevance
“…Protein identification was performed by peptide mass fingerprinting [ 33 , 34 ] using an Ultraflex III MALDI-TOF/TOF mass spectrometer (Bruker Daltonics, Billerica, MA). Bands and spots of interest were manually excised, destained, as previously described [ 34 , 35 ], and acetonitrile dehydrated. Before protein digestion, 1D gel-resolved proteins were reduced and alkylated as previously reported [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein identification was performed by peptide mass fingerprinting [ 33 , 34 ] using an Ultraflex III MALDI-TOF/TOF mass spectrometer (Bruker Daltonics, Billerica, MA). Bands and spots of interest were manually excised, destained, as previously described [ 34 , 35 ], and acetonitrile dehydrated. Before protein digestion, 1D gel-resolved proteins were reduced and alkylated as previously reported [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bands and spots of interest were manually excised, destained, as previously described [ 34 , 35 ], and acetonitrile dehydrated. Before protein digestion, 1D gel-resolved proteins were reduced and alkylated as previously reported [ 35 ]. 1D and 2D-gel resolved proteins were rehydrated in trypsin solution (Sigma Aldrich, Italy), and in-gel protein digestion was performed by an overnight incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In consideration of the relative high cytotoxity of filipin to plant cells ( Ovečka et al, 2010 ; Boutté et al, 2011 ), we have used di-4-ANEPPDHQ as an optimal probe to visualize and quantify the lipid order in membranes of living plant cells ( Zhao et al, 2015 ). Moreover, di-4-ANEPPDHQ was used for imaging pf polarly growing pollen tubes as well, and it was clearly reported that the apical regions of Nicotiana tabacum, Picea meyeri have significant higher GP values than other regions ( Liu et al, 2009 ; Moscatelli et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been proposed that sterols in DRMs provide a primer for cellulose biosynthesis ( Peng et al, 2002 ) or a scaffold to ensure the proper structural conformation of CESA and to stabilize CSCs ( Schrick et al, 2012 ). In pollen tubes, DRMs containing actin and tubulin, together with proteins involved in membrane trafficking, have been identified ( Moscatelli et al, 2015 , paper in press). Further functional studies are necessary to elucidate the role of membrane microdomains in exo-endocytosis and in cytoskeleton dynamics.…”
Section: Microtubules and Cell Wall Depositionmentioning
confidence: 99%
“…The presence of CalS in the pollen tube tip ( Cai et al, 2011 ) where callose is absent intriguingly suggests that CalS activity could be controlled by the retrieval of the enzyme from the apical PM to be repositioned in the shank and that MTs could be involved in this process. Even if CalS has not been identified in tobacco pollen tube membrane microdomains ( Moscatelli et al, 2015 ), further studies could better characterize DRM-proteins and investigate the role of MTs in functional relationships between membrane rafts, membrane trafficking and cell wall composition in polarized growth.…”
Section: Microtubules and Cell Wall Depositionmentioning
confidence: 99%